Implementasi pengajaran Adab di Kuttab Ummul Quro - Hamka, Muhammad; Alim, Akhmad (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Education is a fundamental aspect that should be accessible to all human beings on earth, especially the children of the Indonesian nation. Through education, the Indonesian nation can cultivate high-quality scholarly character. The importance of ethical and moral values in education is key to advancing civilization in navigating life on this planet. Present-day education is closely linked to the goals of national education, one of which is to nurture the potential of students with noble character. Character education is regulated through the method of teaching etiquette implemented by several educational institutions, especially in Indonesia. For example, Kuttab Ummul Quro Cibinong aims to produce well-mannered and morally upright students or graduates. They employ the method of teaching etiquette through exemplary behavior, habituation, motivation, and prayer as the weapons of the faithful. This research aims to evaluate the extent to which the method of teaching etiquette is applied by these two educational institutions. This field research method involves interviews, observations, and literature reviews as the main approaches. It is hoped that the results of this research can provide a clear description of the method of teaching etiquette at Kuttab Ummul Quro. Through identifying deficiencies in the applied teaching methods, researchers hope to provide relevant thought contributions that can be further developed in the school. Thus, it is expected to improve the quality of character education desired by the community and educators in Indonesia. Abstrak Pendidikan merupakan hal fundamental yang harus diakses oleh seluruh umat manusia di bumi, terutama anak bangsa Indonesia. Melalui pendidikan, bangsa Indonesia dapat membentuk karakter keilmuan yang berkualitas. Pentingnya nilai-nilai etika dan moralitas dalam pendidikan menjadi kunci untuk memajukan peradaban dalam menjalani kehidupan di bumi ini. Pendidikan saat ini memiliki hubungan erat dengan tujuan pendidikan nasional, salah satunya adalah menciptakan potensi peserta didik yang berakhlak mulia. Pendidikan karakter diatur melalui metode pengajaran adab yang diimplementasikan oleh beberapa institusi pendidikan, terutama di Indonesia. Contohnya, Kuttab Ummul Quro Cibinong memiliki tujuan untuk menghasilkan peserta didik atau lulusan yang beradab dan berakhlak mulia. Mereka menggunakan metode pengajaran adab melalui keteladanan, pembiasaan, motivasi, dan doa sebagai senjata orang beriman. Penelitian ini bertujuan untuk mengevaluasi sejauh mana metode pengajaran adab yang diterapkan oleh dua institusi pendidikan tersebut. Metode penelitian lapangan ini melibatkan wawancara, observasi, dan kajian pustaka sebagai pendekatan utama. Harapannya, hasil penelitian ini dapat memberikan deskripsi yang jelas tentang metode pengajaran adab di Kuttab Ummul Quro. Melalui identifikasi kekurangan dalam metode pengajaran yang diterapkan, peneliti berharap dapat memberikan sumbangan pemikiran yang relevan dan dapat dikembangkan lebih lanjut di sekolah tersebut. Dengan demikian, diharapkan dapat meningkatkan kualitas pendidikan karakter yang diinginkan oleh masyarakat dan pendidik di Indonesia.